Outsourcing sebagai Pelanggaran Terhadap Hak Para Pekerja di Indonesia - Zaimah Husin (Jurnal Kajian Pembaruan Hukum, 2021)
The problem experienced by contract workers or outsourcing are quite varied, which includes the potential of human rights violations. This is because the insufficient existing regulations in Indonesia protect contract workers. This study is legal research, which uses statutory and conceptual approaches that utilize primary, secondary, and tertiary legal materials. The technique of collecting legal materials in this legal research uses literature study. This study shows that outsourcing workers are the most disadvantaged party in a work agreement, remarkably where they are terminated. The outsourcing worker will not get the normative rights like ordinary workers. Outsourced workers do not have a fixed work period. Then, the working period returns to the beginning when a work contract agreement occurs. The work contract system with probation conducted by the company directly benefits the company. It can violate human rights due to the absence of wages based on the length of work provided by the company. As a result, it is essential to pay attention to agency workers' conditions to obtain legal protection for human rights. Human rights are fundamental and must be legally protected. Thus, legal protection regarding the rights of outsourced workers can be carried out by the local government by issuing policies that regulate legal protection for agency workers. Finally, companies will pay more attention to the welfare of workers. KEYWORDS: Outsourcing Workers, Right to Work, Legal Protection.